Paris Climate Agreement: Beacon of Hope (2017)
On 11 November 2014, a remarkable event occurred. President Barack Obama of the United States and President Xi Jinping of China announced a bilateral agree- ment to reduce the emission of greenhouse gases (GHGs) that cause global warming by their respective nations. On 12 December 2015, a year and a month later, repre- sentatives of 195 countries attending the 21st Conference of the Parties of the United Nations Framework Convention on Climate Change meeting in Paris, France, announced the Paris Climate Agreement. The goal of the Paris Climate Agreement is to limit the future emission of GHGs such that the rise in global mean surface temperature will be no more than 1.5 °C (target) or 2.0 °C (upper limit) above the pre-industrial level. The Paris Climate Agreement utilizes an approach for reducing the emissions of GHGs that is dis- tinctly different than earlier efforts. The approach for Paris consists of a series of Intended Nationally Determined Contributions (INDCs), submitted by the world’s nations, reflecting either a firm commitment (unconditional INDCs) or a plan con- tingent on financial and/or technological support (conditional INDCs). The Obama–Xi announcement was instrumental in the framing of the Paris Climate Agreement. The INDCs submitted by the USA and China were built closely upon the November 2014 bilateral announcement. China and the USA rank number one and two, respectively, in terms of national emission of GHGs. Practically speak- ing, unified global action to combat global warming required these two nations to get on the same page.